A COMPARATIVE STUDY OF SCLEROTHERAPY AND HEMORRHOIDECTOMY IN SECOND-DEGREE HEMORRHOIDS - Gahltot, Navratan; Kumar, Ashok; JAKHAR, DIWAN; NATH, KEDAR; Pareek, Monika (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to compare the post-operative complications and outcome of sclerotherapy and hemorrhoidectomy in second-degree hemorrhoids. Methods: A hospital-based prospective comparative study on 100 cases diagnosed to have second-degree hemorrhoids attending emergency or outdoor was taken between December 2021 and November 2022 at the department of Surgery, S.P. Medical College and P.B.M Hospital, Bikaner. Cases were divided into 2 groups SCL group (sclerotherapy group) and H group (hemorrhoidectomy group). Results: The mean age in H group was 38.56±7.8 years whereas 39.08±8.2 years in SCL group. (p>0.05) and both groups were sociodemographically comparable. The mean duration of hospital stay in H group was 1.5±0.4 days whereas 0.9±0.3 day in SCL group (p<0.05). In H group, maximum 96.00% had complaints of pain and 30% had bleeding whereas in SCL maximum of 66.00% had complaints of bleeding and 38% had constipation. In H group, maximum 74% were cured whereas 96% in the group SCL (p=0.005*). Conclusion: The findings of the study conclude that of the two surgical procedures employed in the study to treat hemorrhoids sclerotherapy was found to had less complications, early ambulation, short post-operative hospital stay, and cost-effective.